Degradable composite film paper material and preparation method thereof

By using polymer layers of polylactic acid, polycaprolactone and new synergists in composite film paper, combined with paper layer, and processing by hot pressing composite and cold pressing rollers, the problem of insufficient mechanical properties and antibacterial properties of existing composite film paper is solved, and a high-strength and excellent antibacterial properties of degradable composite film paper materials are achieved.

CN119570222AActive Publication Date: 2025-03-07GUANGDONG DAOKE NEW MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411753235.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-07
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

The shortcomings of existing composite film papers in mechanical properties and antibacterial properties have limited their wide application in the packaging field, especially in the context of increasing food safety and environmental protection requirements.

Method used

A polymer layer including polylactic acid, polycaprolactone and a novel synergist was used, combined with the paper layer, and the degradable composite film paper material with excellent antibacterial properties and good mechanical properties was prepared by hot pressing composite and cold pressing roller treatment.

Benefits of technology

The antibacterial level has been achieved to reach level 0, the tensile strength is 30-34MPa, and the elongation of break is 415-450%, which significantly improves the mechanical properties and antibacterial properties of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119570222A_ABST
    Figure CN119570222A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of packaging materials, and particularly relates to a degradable composite film paper material and a preparation method thereof. The degradable composite film paper material comprises a polymer layer and a paper layer, and the polymer layer comprises the following components in parts by weight: 70-80 parts of polylactic acid, 20-30 parts of polycaprolactone, 1-3 parts of a synergist, 8-10 parts of citrate starch, 0.3-1.0 part of a lubricant and 0.2-0.5 part of an antioxidant. Experimental results show that the antibacterial grade of the degradable composite film paper material prepared by the invention is 0 grade, the tensile strength is 30-34 MPa, and the elongation at break is 415-450%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of packaging materials, and in particular relates to a degradable composite film paper material and a preparation method thereof. Background Art

[0002] As a new green and sustainable packaging material, degradable film paper not only meets the market's urgent demand for environmentally friendly products, but also provides manufacturers, brand owners and consumers with a more environmentally friendly and practical packaging option, which has a far-reaching impact on promoting green development of society.

[0003] Prior art CN107902258A discloses a fully degradable paper-plastic composite film paper and a preparation method thereof, wherein the composite film paper comprises a polylactic acid film layer, an adhesive layer and a paper layer, has fully biodegradable properties, and effectively reduces the environmental pollution caused by petrochemical plastic products, but its main focus is on improving the mechanical properties of the composite film paper. CN103538317A discloses a composite film, especially a high-strength paper-plastic composite film, which enhances the tensile strength and heat-sealing strength by combining a kraft paper film layer, a polyester film layer, an aluminum foil layer and a polyethylene film layer, and optimizes the anti-breakage performance of the transport bag during a fall, but its focus is also on improving the mechanical properties, and has not made a significant contribution to the improvement of the antibacterial properties.

[0004] The shortcomings of existing composite film papers in mechanical properties and antibacterial properties limit their wide application in the packaging field. Especially in the context of the current market's increasing requirements for food safety and environmental protection, it is particularly important to develop a composite film paper that can maintain good mechanical properties and have excellent antibacterial properties. This material can not only reduce or avoid the use of chemical preservatives, but also further improve food safety and packaging environmental friendliness. Summary of the invention

[0005] In order to overcome the deficiencies of the prior art, one of the objectives of the present invention is to provide a degradable composite film paper material having good degradability and antibacterial properties.

[0006] One of the purposes of the present invention is achieved by the following technical solution:

[0007] A degradable composite film-paper material comprises a polymer layer and a paper layer, wherein the polymer layer comprises the following components by weight: 70 to 80 parts of polylactic acid, 20 to 30 parts of polycaprolactone, 1 to 3 parts of a synergist, 8 to 10 parts of citrate starch, 0.3 to 1.0 parts of a lubricant, and 0.2 to 0.5 parts of an antioxidant; the synergist has the following structure:

[0008]

[0009] Furthermore, the preparation process of the synergist comprises the following steps:

[0010]

[0011] (1) 1,2-bis(2-iodoethoxy)ethane and 1-methyl-1H-imidazole-4-carboxaldehyde are added to acetonitrile and reacted at 85-95° C. for 16-24 hours, and then treated to obtain intermediate 1;

[0012] (2) intermediate 1, inorganic base and S8 are added to methanol and reacted at 70-90°C for 36-48h, and then treated to obtain intermediate 2;

[0013] (3) intermediate 2 and iodomethane are added to N,N-dimethylformamide and reacted at 25-35°C for 16-24 hours, and then treated to obtain intermediate 3;

[0014] (4) The intermediate 3 and phenylethylamine are added to methanol and reacted at 25-35°C for 6-12 hours, and then treated to obtain a synergist.

[0015] Furthermore, the molar ratio of 1,2-bis(2-iodoethoxy)ethane to 1-methyl-1H-imidazole-4-carbaldehyde in step (1) is 1:(2-2.5).

[0016] Furthermore, in step (2), the molar ratio of the intermediate 1, the inorganic base and S8 is 1:(2.5-4):(2-2.5); the inorganic base is one of potassium carbonate and cesium carbonate.

[0017] Furthermore, in step (3), the molar ratio of the intermediate 2 to methyl iodide is 1:(5-7).

[0018] Furthermore, in step (4), the molar ratio of the intermediate 3 to phenylethylamine is 1:(1.1-1.3).

[0019] Furthermore, the antioxidant is antioxidant 1076, and the lubricant is ethylene bisstearamide EBS.

[0020] Furthermore, the specification of the polycaprolactone is CAPA6800, and the specification of the polylactic acid is 4032D.

[0021] A second object of the present invention is to provide a method for preparing a degradable composite film paper material.

[0022] The second object of the present invention is achieved by adopting the following technical solution:

[0023] The method for preparing the above-mentioned degradable composite film paper material comprises the following steps:

[0024] S1: adding polylactic acid, polycaprolactone, synergist, citrate starch, lubricant and antioxidant into a casting machine according to the ratio, mixing for 1-2 hours and then extruding into a film to obtain a polymer layer;

[0025] S2: The paper and the polymer are firstly laminated by hot pressing with a hot pressing roller, and then flattened with a cold pressing roller to obtain a degradable composite film paper material.

[0026] Furthermore, the film forming temperature in step S1 is 60-70°C.

[0027] Furthermore, in step S2, the temperature of the hot pressing roller is 130-170° C., and the pressure is 0.2-0.5 MPa; the temperature of the cold pressing roller is 20-25° C., and the pressure is 0.05-0.10 MPa.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] 1. The present invention provides a degradable composite film paper material, comprising a paper layer and a polymer layer. The polymer layer is based on the characteristics of polylactic acid and polycaprolactone being degradable in the natural environment, and a new type of synergist is added to solve the problem of insufficient mechanical properties and poor antibacterial properties of polylactic acid / polycaprolactone composite film. Experimental results show that the antibacterial grade of the degradable composite film paper material prepared by the present invention is 0, the tensile strength is 30-34MPa, and the elongation at break is 415-450%.

[0030] 2. Through careful molecular design, the synergist prepared by the present invention contains more active functional groups, such as quaternary ammonium cations, imine groups, thioether bonds, etc., wherein the quaternary ammonium cations can be adsorbed onto the negatively charged bacterial cell membrane to achieve the purpose of antibacterial, and the imine bonds (C=N) can form hydrogen bonds with the carboxyl and hydroxyl groups in the PLA molecules, significantly improving the interaction force between molecules, thereby enhancing the mechanical properties of the material; the thioether bonds can chemically react or physically adsorb with the hydroxyl groups on the surface of the cellulose paper to form a strong interface bonding force. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 It is a flow chart of the preparation of the synergist of the present invention. DETAILED DESCRIPTION

[0032] Below, in conjunction with the accompanying drawings and specific embodiments, the present invention is further described. It should be noted that, under the premise of no conflict, the embodiments described below or the technical features can be arbitrarily combined to form new embodiments. The specific conditions not specified in the embodiments are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, unless otherwise specified, are conventional products obtained through commercial channels.

[0033] Example 1

[0034] A degradable composite film paper material comprises the following components by weight: 70 parts of polylactic acid, 30 parts of polycaprolactone, 2 parts of synergist, 9 parts of citrate starch, 0.6 parts of ethylene bisstearamide, and 0.3 parts of antioxidant 1076.

[0035] The preparation process of the synergist is as follows Figure 1 As shown, the following steps are included:

[0036] (1) 1,2-bis(2-iodoethoxy)ethane (0.1 mol) and 1-methyl-1H-imidazole-4-carboxaldehyde (0.22 mol) were added to 300 mL of acetonitrile and reacted at 90° C. for 18 h; the reaction solution was filtered and the filtrate was concentrated, and the concentrated crude product was dissolved in 30 mL of dichloromethane, filtered and concentrated to obtain intermediate 1;

[0037] (2) Intermediate 1 (0.1 mol), potassium carbonate (0.32 mol), and S8 (0.22 mol) were added to 150 mL of methanol and reacted at 80° C. for 36 h. The reaction solution was filtered and the filtrate was concentrated. The concentrated crude product was dissolved in 30 mL of dichloromethane and filtered and concentrated to obtain Intermediate 2.

[0038] (3) Intermediate 2 (0.1 mol) and iodomethane (0.6 mol) were added to 300 mL of N,N-dimethylformamide and reacted at 30°C for 18 h. The mixture was concentrated to obtain intermediate 3.

[0039] (4) Intermediate 3 (0.1 mol) and phenylethylamine (0.12 mol) were added to 250 mL of methanol and reacted at 30° C. for 10 h. The reaction solution was filtered and the filter cake was dried to obtain a synergist.

[0040] Hydrogen spectrum results of the synergist: 1 H NMR (C 34 H 46 I2N6O2S2, 400MHz, DMSO-d6): δ8.28 (s, 2H), 7.76 (s, 2H), 7.25-7.17 (m, 10H), 4.40-4 .32(m, 10H), 3.85(t, 4H), 3.52(s, 4H), 2.90(t, 4H), 2.53-2.60(s, 6H), 1.85(t, 4H).

[0041] The preparation process of the degradable composite film paper material comprises the following steps:

[0042] S1: Polylactic acid and polycaprolactone were dried in a drying oven at 80°C for 24 hours, and the dried polylactic acid, polycaprolactone, synergist, citrate starch, ethylene bisstearamide, and antioxidant 1076 were put into a casting machine according to the ratio, mixed for 1.5 hours, and then extruded through a flat sheet die to form a film at a film forming temperature of 65°C to obtain a polymer layer;

[0043] S2: The paper and the above polymer are firstly hot-pressed and laminated by a hot pressing roller at 150°C and 0.4MPa for 3s, and then flattened by a cold pressing roller at 22°C and 0.07MPa to obtain a degradable composite film paper material.

[0044] Example 2

[0045] A degradable composite film paper material comprises the following components by weight: 80 parts of polylactic acid, 20 parts of polycaprolactone, 3 parts of synergist, 8 parts of citrate starch, 0.3 parts of ethylene bisstearamide, and 0.2 parts of antioxidant 1076.

[0046] The preparation process of the synergist comprises the following steps:

[0047] (1) 1,2-bis(2-iodoethoxy)ethane (0.1 mol) and 1-methyl-1H-imidazole-4-carboxaldehyde (0.25 mol) were added to 300 mL of acetonitrile and reacted at 85° C. for 24 h; the reaction solution was filtered and the filtrate was concentrated, and the concentrated crude product was dissolved in 30 mL of dichloromethane, filtered and concentrated to obtain intermediate 1;

[0048] (2) Intermediate 1 (0.1 mol), potassium carbonate (0.4 mol), and S8 (0.22 mol) were added to 150 mL of methanol and reacted at 70° C. for 48 h. The reaction solution was filtered and the filtrate was concentrated. The concentrated crude product was dissolved in 30 mL of dichloromethane and filtered and concentrated to obtain Intermediate 2.

[0049] (3) Intermediate 2 (0.1 mol) and iodomethane (0.7 mol) were added to 300 mL of N,N-dimethylformamide and reacted at 25°C for 24 h. The mixture was concentrated to obtain intermediate 3.

[0050] (4) Intermediate 3 (0.1 mol) and phenylethylamine (0.13 mol) were added to 250 mL of methanol and reacted at 25° C. for 12 h. The reaction solution was filtered and the filter cake was dried to obtain a synergist. The hydrogen spectrum of the synergist showed that its structure was consistent with that of Example 1.

[0051] The preparation process of the degradable composite film paper material comprises the following steps:

[0052] S1: Polylactic acid and polycaprolactone were dried in a drying oven at 80°C for 24 hours, and the dried polylactic acid, polycaprolactone, synergist, citrate starch, ethylene bisstearamide, and antioxidant 1076 were put into a casting machine according to the ratio, mixed for 2 hours, and then extruded through a flat sheet die to form a film at a film forming temperature of 70°C to obtain a polymer layer;

[0053] S2: The paper and the above polymer are firstly hot-pressed and laminated by a hot pressing roller at 170°C and 0.5 MPa for 4 seconds, and then flattened by a cold pressing roller at 25°C and 0.10 MPa to obtain a degradable composite film paper material.

[0054] Example 3

[0055] A degradable composite film paper material comprises the following components by weight: 75 parts of polylactic acid, 25 parts of polycaprolactone, 1 part of a synergist, 10 parts of citrate starch, 1.0 part of ethylene bisstearamide, and 0.5 part of an antioxidant 1076.

[0056] The preparation process of the synergist comprises the following steps:

[0057] (1) 1,2-bis(2-iodoethoxy)ethane (0.1 mol) and 1-methyl-1H-imidazole-4-carboxaldehyde (0.2 mol) were added to 300 mL of acetonitrile and reacted at 95° C. for 16 h; the reaction solution was filtered and the filtrate was concentrated, and the concentrated crude product was dissolved in 30 mL of dichloromethane, filtered and concentrated to obtain intermediate 1;

[0058] (2) Intermediate 1 (0.1 mol), potassium carbonate (0.25 mol), and S8 (0.2 mol) were added to 150 mL of methanol and reacted at 90° C. for 36 h. The reaction solution was filtered and the filtrate was concentrated. The concentrated crude product was dissolved in 30 mL of dichloromethane and filtered and concentrated to obtain Intermediate 2.

[0059] (3) Intermediate 2 (0.1 mol) and iodomethane (0.5 mol) were added to 300 mL of N,N-dimethylformamide and reacted at 35°C for 16 h. The mixture was concentrated to obtain intermediate 3.

[0060] (4) Intermediate 3 (0.1 mol) and phenylethylamine (0.11 mol) were added to 250 mL of methanol and reacted at 35° C. for 6 h. The reaction solution was filtered and the filter cake was dried to obtain a synergist. The hydrogen spectrum of the synergist showed that its structure was consistent with that of Example 1.

[0061] The preparation process of the degradable composite film paper material comprises the following steps:

[0062] S1: Polylactic acid and polycaprolactone were dried in a drying oven at 80°C for 24 hours, and the dried polylactic acid, polycaprolactone, synergist, citrate starch, ethylene bisstearamide, and antioxidant 1076 were put into a casting machine according to the ratio, mixed for 1 hour, and extruded through a flat sheet die to form a film at a film forming temperature of 60°C to obtain a polymer layer;

[0063] S2: The paper and the above polymer are firstly hot-pressed and laminated by a hot pressing roller at 130°C and 0.2MPa for 2s, and then flattened by a cold pressing roller at 20°C and 0.05MPa to obtain a degradable composite film paper material.

[0064] Comparative Example 1

[0065] A degradable composite film paper material, which differs from Example 1 in that a synergist is omitted.

[0066] Test example

[0067] The degradable composite film paper materials prepared in Examples 1 to 3 and Comparative Example 1 were subjected to peeling force test, mechanical property test, antibacterial property test and barrier property test. The results are shown in Table 1.

[0068] The test method is: test the peel force according to GB / T 36392-2018 "Laminated paper and paperboard for food packaging"; test the tensile strength according to GB / T1040.3-2006 standard, and the test rate is 250mm / min; test the antibacterial property according to QB / T2591-2003 "Test method and antibacterial effect of antibacterial plastics"; determine the oxygen permeability of degradable composite film and paper materials according to GB / T1038-2000 "Plastic film and sheet gas permeability test method pressure difference method", and the test conditions are 23℃, 0%RH; determine the water vapor permeability of degradable composite film and paper materials according to the national standard GB / T1037-88 "Plastic film and sheet water vapor permeability test method cup method", and the test conditions are 38℃, 90%RH.

[0069] Table 1 Performance results of the degradable composite film paper materials of Examples 1 to 3 and Comparative Example 1

[0070]

[0071] It can be seen from Table 1 that the degradable composite film paper materials prepared in Examples 1-3 of the present invention have excellent mechanical properties, peeling force and barrier properties, and their antibacterial grade can reach the best grade 0.

[0072] Compared with the comparative example 1 without adding the synergist, the antibacterial property, mechanical strength and peel strength of the examples 1-3 are significantly improved, which shows that the synergist synthesized by the present invention has the effect of improving the insufficient mechanical properties and poor antibacterial property of the PLA / PCL composite film paper. The quaternary ammonium cation in the synergist designed and synthesized by the present invention can achieve the purpose of antibacterial by adsorbing on the negatively charged bacterial cell membrane, and the imine bond (C=N) can form a hydrogen bond with the carboxyl group and the hydroxyl group in the PLA molecule, thereby enhancing the mechanical properties of the material; the thioether bond can react chemically or physically adsorb with the hydroxyl group and other groups on the surface of the cellulose paper to form a strong interface bonding force.

[0073] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.

Claims

1. A degradable composite film paper material, characterized in that: The invention comprises a polymer layer and a paper layer, wherein the polymer layer comprises the following components by weight: 70 to 80 parts of polylactic acid, 20 to 30 parts of polycaprolactone, 1 to 3 parts of synergist, 8 to 10 parts of citrate starch, 0.3 to 1.0 parts of lubricant, and 0.2 to 0.5 parts of antioxidant; the structure of the synergist is:

2. The degradable composite film paper material according to claim 1, characterized in that: The preparation process of the synergist comprises the following steps: (1) 1,2-bis(2-iodoethoxy)ethane and 1-methyl-1H-imidazole-4-carboxaldehyde are added to acetonitrile and reacted at 85-95° C. for 16-24 hours, and then treated to obtain intermediate 1; (2) intermediate 1, inorganic base and S8 are added to methanol and reacted at 70-90°C for 36-48h, and then treated to obtain intermediate 2; (3) intermediate 2 and iodomethane are added to N,N-dimethylformamide and reacted at 25-35°C for 16-24 hours, and then treated to obtain intermediate 3; (4) The intermediate 3 and phenylethylamine are added to methanol and reacted at 25-35°C for 6-12 hours, and then treated to obtain a synergist.

3. The degradable composite film paper material according to claim 2, characterized in that: The molar ratio of 1,2-bis(2-iodoethoxy)ethane to 1-methyl-1H-imidazole-4-carbaldehyde in step (1) is 1:(2-2.5).

4. The degradable composite film paper material according to claim 2, characterized in that: In step (2), the molar ratio of the intermediate 1, the inorganic base and S8 is 1:(2.5-4):(2-2.5); the inorganic base is one of potassium carbonate and cesium carbonate.

5. The degradable composite film paper material according to claim 2, characterized in that: In step (3), the molar ratio of the intermediate 2 to methyl iodide is 1:(5-7).

6. The degradable composite film paper material according to claim 2, characterized in that: In step (4), the molar ratio of the intermediate 3 to phenylethylamine is 1:(1.1-1.3).

7. The degradable composite film paper material according to claim 1, characterized in that: The antioxidant is antioxidant 1076, and the lubricant is ethylene bisstearamide.

8. The method for preparing the degradable composite film paper material according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1: adding polylactic acid, polycaprolactone, synergist, citrate starch, lubricant and antioxidant into a casting machine according to the ratio, mixing for 1-2 hours and then extruding into a film to obtain a polymer layer; S2: The paper and the polymer are firstly laminated by hot pressing with a hot pressing roller, and then flattened with a cold pressing roller to obtain a degradable composite film paper material.

9. The method for preparing the degradable composite film paper material according to claim 8, characterized in that: The film forming temperature in step S1 is 60-70°C.

10. The method for preparing the degradable composite film paper material according to claim 8, characterized in that: In step S2, the temperature of the hot pressing roller is 130-170°C, and the pressure is 0.2-0.5MPa; the temperature of the cold pressing roller is 20-25°C, and the pressure is 0.05-0.10MPa.

Citation Information

Patent Citations

  • High-strength paper-plastic composite membrane

    CN103538317A

  • Full-degradable paper-plastic composite film paper and preparation method thereof

    CN107902258A

  • Biodegradable PE-coated paper material and preparation method thereof

    CN102558797A

  • Preparation method of antibacterial and wear-resistant plastic used by children toys

    CN110041678A

  • PLA coated paper and preparation method thereof

    CN110184854A

Cited By

  • High-toughness degradable polylactic acid film as well as preparation process and application thereof

    CN121108706A